2017
DOI: 10.1109/tac.2016.2594169
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in Bidirectional Platoons With Dynamic Controllers and Proportional Asymmetry

Abstract: Abstract-We consider platoons composed of identical vehicles with an asymmetric nearest-neighbor interaction. We restrict ourselves to intervehicular coupling realized with dynamic arbitrary-order onboard controllers such that the coupling to the immediately preceding vehicle is proportional to the coupling to the immediately following vehicle. Each vehicle is modeled using a transfer function and we impose no restriction on the order of the vehicle. The platoon is described by a transfer function in a conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Also, in accordance to e.g. (Hao et al, 2012;Herman et al, 2017b;Nieuwenhuijze, 2010), we found in the simulations that the bidirectional control exhibits a better disturbance rejection for both the position and speed deviations (that is, the peak of the position deviation is observed to be at 2.2 m for ε i = 0 and at 1.9 m for ε i = 1, and the peak of the speed deviation is observed to be at 1.9 m s −1 for ε i = 0 and at 1.7 m s −1 for ε i = 1).…”
Section: Numerical Validationsupporting
confidence: 89%
“…Also, in accordance to e.g. (Hao et al, 2012;Herman et al, 2017b;Nieuwenhuijze, 2010), we found in the simulations that the bidirectional control exhibits a better disturbance rejection for both the position and speed deviations (that is, the peak of the position deviation is observed to be at 2.2 m for ε i = 0 and at 1.9 m for ε i = 1, and the peak of the speed deviation is observed to be at 1.9 m s −1 for ε i = 0 and at 1.7 m s −1 for ε i = 1).…”
Section: Numerical Validationsupporting
confidence: 89%
“…For large-scale networks, an emerging approach to understanding fundamental limitations while overcoming the nonconvexity difficulty is to derive asymptotic bounds on the best achievable performance [1], [12]- [18]. In particular, the approach taken in [1] is to study performance of distributed static state-feedback controllers with locality constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present a brief summary of the SWOT for the regional market segment since based on the results of the stated preference survey (see Section IV.A), this market is the most VC-attractive to railway customers. The analyses for the other market segments (including freight) can be found in [11].…”
Section: B Sme Opinionsmentioning
confidence: 99%